Development Strategy of Non-Timber Forest Product Multi-Business Forestry In Social Forestry Partnership - Hardjanto, Hardjanto; Safitri, Yuniar; Sundawati, Leti (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Indonesia’s forest area is decreasing every year, and the high pressure from the community has caused massive public access to forests, so there is a need for solutions to overcome tenure problems and community welfare. The policies offered as a solution is social forestry with a multibusiness forestry system. The research aims are to formulate multi-business NTFP utilization development strategies. The analysis used the SWOT and AHP combination methods to formulate the best possible development strategy. Based on the research conducted, the best strategy for developing multi-business NTFPs utilization is a growth-oriented strategy that focuses on SO strategy, as follows: increasing the number of species combinations, business diversification, taking advantage of FMUs and local government’s role in supporting the diversification of NTFPs utilization, actively involved in sharing information which is carried out both to fellow members and outside parties, promotion of products or commodities to expanding the market and attracting investors, and empowerment through community institutions with assistance and training. The strategies are expected to improve the quality of the forest and community welfare so that the main functions of the forest are maintained but still provide benefits to the community.